2015
DOI: 10.16888/interd.2015.32.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Equivalencia factorial del Cuestionario de Agresores / Victimas de Olweus según género

Abstract: Este trabajo aborda un tema de gran actualidad, pero escasamente evaluado con investigaciones científico-empíricas en la Argentina: el bullying. El Cuestionario Revisado de Agresores / Víctimas de Olweus es uno de los instrumentos más usados en el mundo para medir el ser acosado y acosar a otros alumnos, ya que tiende a funcionar similarmente en las distintas naciones. Estudios extranjeros y preliminares en la Argentina detectaron que dicho cuestionario presenta una dimensión unifactorial tanto para la Escala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
2
0
6
Order By: Relevance
“…On the other hand, in the perpetration subscale, the item "I was threatened or forced" had the highest alpha score. Several studies have found different discrimination items (Breivik and Olweus, 2015;Resett et al, 2015), highlighting the importance of performing validation studies in different countries to take into account cultural differences. On the other hand, in both subscales, the IRT analysis showed that the item with the lowest-severity parameter was "I was called mean names" and "I called another student(s) mean names, " which may be explained because verbal aggression is one of the most common forms of bullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the perpetration subscale, the item "I was threatened or forced" had the highest alpha score. Several studies have found different discrimination items (Breivik and Olweus, 2015;Resett et al, 2015), highlighting the importance of performing validation studies in different countries to take into account cultural differences. On the other hand, in both subscales, the IRT analysis showed that the item with the lowest-severity parameter was "I was called mean names" and "I called another student(s) mean names, " which may be explained because verbal aggression is one of the most common forms of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…The perpetration scale had a Cronbach's alpha of 0.81, and the lowest item-total correlation was for threatening others (r = 0.16). In another study with 1,222 Argentinean students, a good fit for the two-factor model of the OBVQ-R (being bullied and bullying others) using confirmatory factorial analysis (CFA) was found (Resett et al, 2015). Additionally, the study found differences in the perpetrator subscale between genders, observing that boys identified themselves as harming others by physical aggression, and girls by relational aggression (e.g., lying, spreading rumors).…”
Section: The Olweus Bully/victim Questionnairementioning
confidence: 93%
“…Sin embargo, dado que la muestra utilizada en este trabajo estuvo conformada en gran medida por trabajadores provenientes del sector privado, sería útil replicar la estructura factorial con muestras de trabajadores pertenecientes a otros sectores. También sería deseable realizar análisis factorial confirmatorio multigrupo (Resett, Costa, Murata & Falcone, 2015) que permita determinar la equivalencia del modelo bifactorial de burnout en diferentes ocupaciones, y ofrecer de esta manera evidencia que sustente la validez de las conclusiones basadas en las comparaciones entre diferentes grupos ocupacionales. Por último, se ha señalado que el contenido de algunos ítems del MBI-GS podría ser sensible al sesgo de deseabilidad social (Kristensen et al, 2005) afectando, por consiguiente, la validez de las respuestas (Merino Soto & Vilcherrez Pizarro, 2014).…”
Section: Discussionunclassified
“…Consta de 40 preguntas cuyo propósito es indagar acerca de problemas en relación a: agredir/ser agredido, tipos y formas de violencia, frecuencias de las distintas formas de agresión y de ser agredido, lugares donde ocurre la agresión y las actitudes frente a la agresión. Se utilizó una adaptación realizada para población argentina (Resett, 2011;Resett, Costa, Murata y Falcone, 2015) cuya validez como instrumento de medición ha alcanzado valores de Alfa de Cronbach de 0,80 a 0,90. El cuestionario incluye preguntas específi cas para agresores y víctimas, a partir de las cuales se determina la presencia de bullying según la frecuencia y la duración de las agresiones.…”
Section: Instrumentosunclassified